The application of CIRAM risk analysis for integrated border management in the Guardia Civil - Sánchez Calero, Cristina (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2025)
In 2019, the European Union imposed on Member States the adoption of the CIRAM method for risk analysis at borders. This dissertation evaluates the impact of this Regulation in Spain, particularly in Guardia Civil, analyzing its applicability in all border competences. After interviews and documentary analysis, it is confirmed that even if an integrated border management is not applied at national level, CIRAM is already implemented centrally in Guardia Civil, but its peripheral application needs improvement. Furthermore, it is feasible to implement CIRAM in all its border activities, but we cannot confirm that it facilitates decision-making and resource management as it is not yet fully considered completely in all the units involved in borders.
Keywords: integrated border management; risk analysis; Guardia Civil; external borders; CIRAM